Voltage Sag And Swell Mitigation Using Grey Wolf Optimizer (Gwo) For A Single-Phase Grid-Connected Photovoltaic System - Jeff Collven, Claisdell Lorren (2022)
The most prominent power quality challenges affecting distribution networks are voltage sag and swell, especially in sectors where losses can be significant. The reason that the power quality issue must be resolved as soon as possible is that high power quality may save money and energy. Lower energy costs and reactive power pricing provide direct benefits to customers. Indirect savings are realized by avoiding situations such as equipment damage and premature aging, productivity loss, and data and work loss. The main objective of this research is to design a simple control strategy by using the Proportional Integral-Grey Wolf Optimizer (PI-GWO) to mitigate voltage sag and swell during weak grid conditions. The research presents a newly developed and efficient optimization technique called GWO for the first time to solve power quality disturbances in single-phase grid-connected systems. Grey wolf optimization (GWO) is a new meta-heuristic optimization approach based on the influence of wolves' natural leadership hierarchy and hunting mechanism. The proposed design required the photovoltaic (PV) array to be connected to a single-phase grid-connected system. First, a 5MW photovoltaic power supply is developed before being connected to the grid. Then, at the grid section, voltage sag and swell configurations are applied to show the single-phase faults that normally occur in the grid – voltage sag and swell. PI-GWO is introduced into the system to mitigate the power quality issue and analyze its effectiveness under different percentages of voltage sag and swell. It is found that the 10% and 20% of voltage sag and swell could be mitigate by using PI-GWO controller for a single-phase grid-connected photovoltaic system.